2006
DOI: 10.1108/14608790200600018
|View full text |Cite
|
Sign up to set email alerts
|

Housing ‘unhoused minds’: inter‐personality disorder in the organisation?

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Single homeless people are hindered by reductions in social housing (Minton, 2017), rising costs in the private rental sector; and the 59 per cent reduction in the supporting people funding in both securing and retaining a home (National Audit Office, 2017). Research into the histories of people experiencing homelessness have found high levels of developmental and compound (repeated) trauma (Cockersell, 2018), which can lead to a state of being “psychologically unhoused”, often expressed through self-neglect, alienation and an inability to transition to and sustain a housed state (Scanlon and Adlam, 2006). Therefore, without appropriate support individuals can struggle to maintain stability in their own homes which can contribute to frequent eviction and the abandonment of housing (Teixeira, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Single homeless people are hindered by reductions in social housing (Minton, 2017), rising costs in the private rental sector; and the 59 per cent reduction in the supporting people funding in both securing and retaining a home (National Audit Office, 2017). Research into the histories of people experiencing homelessness have found high levels of developmental and compound (repeated) trauma (Cockersell, 2018), which can lead to a state of being “psychologically unhoused”, often expressed through self-neglect, alienation and an inability to transition to and sustain a housed state (Scanlon and Adlam, 2006). Therefore, without appropriate support individuals can struggle to maintain stability in their own homes which can contribute to frequent eviction and the abandonment of housing (Teixeira, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On account of histories of trauma and experiences of discrimination, homeless people often present with combinations of vulnerability and volatility and can be ambivalent about receiving help. This, in turn, stimulates over- and under-identification from professionals and creates challenges in building working relationships, managing personal distress and avoiding ‘burn out’ (see Adlam and Scanlon, 2005; Scanlon and Adlam, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of vulnerable groups, Jones et al (2019, p1) identify austerity as a form of "institutional violence" that impacts most heavily on poorer families and children, ethnic minorities, people with disabilities and on other disadvantaged groups including women; and Cooper and Whyte (2017) describe the "toll of death and illness and injury that so-called austerity policies have caused." For clients in supported housing who often suffer multiple disadvantages, austerity means struggling not only with the issues of poverty and exclusion impacting across broader society, but also issues such as substance abuse, histories of offences, and long-term physical and mental illnesses (Scanlon & Adlam, 2006). These often complex and multifaceted needs make such client groups especially vulnerable to change (Jacobs & Manzi, 2013).…”
Section: Supported Housing Vulnerability and Changementioning
confidence: 99%